Visualized tracing of rebar corrosion evolution in concrete with x-ray micro-computed tomography method. (September 2018) - Dong, Biqin; Shi, Guiyun; Dong, Peng; Ding, Weijian; Teng, Xiaojuan; Qin, Shaofeng; Liu, Yuqing; Xing, Feng; Hong, Shuxian
Abstract: A X-ray micro-computed tomography (XCT) imaging method is proposed to measure and analysis the corrosion behavior of rebar in a marine environment. The experimental results reveal that the time-dependent corrosion morphology of rebar in the three-dimensional configuration can be clearly visualized and certain corrosion parameters can be determined. Based on the characteristics analysis of XCT image, the time point of the initial rust and corrosion-induced crack are estimated. Moreover, the whole corrosion process can be divided into three phases as corrosion initiation (chloride penetration), free expansion and cracking, which agrees with the frequently used corrosion model.